MENINGKATKAN MOTIVASI BELAJAR DAN MOTORIK HALUS MENGKOORDINASIKAN MATA DAN TANGAN MENGGUNAKAN MODEL EXPRO - Rahmadani, Nur Indah Putri; Agusta, Akhmad Riandy (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
This research is motivated by the low fine motor skills in coordinating the eyes and hands in children of group A1 of Adhyaksa XIV Kindergarten. To overcome this problem, the Expro model can be used. The purpose of this study is to describe teacher activities, children's activities, learning motivation and the results of children's fine motor development achievements, especially in coordinating the eyes and hands. This approach uses a qualitative approach and Classroom Action Research (CAR) with 4 meetings. The results of the study show that teacher activities have implemented the steps of the learning model with a score of 32 with a percentage of 100% with the Very Good category, children's activities have achieved an increase up to meeting 4 with a percentage of 97% with the Very Active category, children's learning motivation activities have achieved an increase up to meeting 4 with a percentage of 98% with the High category and children's fine motor aspects have achieved an increase up to meeting 4 with a percentage of 100% of children successfully getting the